“Sexual Harassment: It’s Time to Break the Silence and Eliminate the Lies”, 12-13 October 2019 - UiTM, Faculty of Law (Faculty of Law, 2019)
On 12 and 13th October 2019, the UiTMLaw Pro Bono Team was invited to give a talk entitled “Sexual Harassment: It’s Time to Break the Silence and Eliminate the Lies”. The event was held at Dewan Berlian, UiTM Puncak Alam in conjunction with the UiTM Research Fiesta 2019. The team was divided into two. On the first day, the panellists included Associate Professor Dr. Daleleer Kaur, Dr. Nadzriah Ahmad, Dr. Mohd Haris Abd Rani and Puan Mimi Sintia Mohd Bajury. The moderator for the talk was PM Dr. Sheela Jayabalan. On the second day, the moderator was Puan Farizah Mohamed Isa, and the panellists are Associate Professor Dr. Haswira Nor Mohamad Hashim, Dr. Wan Rosalili Wan Rosli and Encik Ahmad Shukree Mohd Salleh.